Discovery of the largest lungless tetrapod, Atretochoana eiselti (Taylor, 1968) (Amphibia: Gymnophiona: Typhlonectidae), in its natural habitat in Brazilian Amazonia - Hoogmoed, Marinus Steven; Maciel, Adriano Oliveira; Coragem, Juliano Tupan (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
We report the occurrence of the limbless and lungless tetrapod, Atretochoana eiselti, in two widely separated Brazilian Amazonian lowland localities, one (Mosqueiro island and Baía de Marajó, Belém) near the mouth of the Amazon river and another (Cachoeira Santo Antônio) near the border between Brazil and Bolivia in the Madeira river. It is shown that this species is not an inhabitant of cool, oxygen rich and fast running water in elevated localities as supposed until now, but on the contrary occurs in warm (24-30 °C), turbid, fast running water in the lowland Brazilian Amazon basin. We describe the probable habitat and three freshly preserved specimens (one male, two females) and compare them to the only two specimens known; some data are provided about the biology of this species, that seems to have a wide distribution in Brazilian Amazonia and possibly also occurs in other countries, like Bolivia.